A 10-year single center survey of pediatric patients with histiocytic disorders in Iran - Shamsian, Bibi Shahin; Nikoufar, Maryam; Esfahani, Shadi Abdar; Shamshiri, Ahmad Reza; Arzanian, Mohammad Taghi; Alavi, Samin; Jadali, Farzaneh; Gharib, Atoosa; Rezaei, Nima (The Turkish Journal of Pediatrics, 2011)
Childhood histiocytosis is a rare and diverse group of proliferative disorders, characterized by accumulation and infiltration of antigen-presenting cells or antigen-processing cells, which can affect any tissue or organ. This study was performed in order to investigate the clinical characteristics of Iranian children with different types of histiocytic disorders. Thirty-five patients, with a median age of 3.5 years, who were referred and diagnosed with histiocytic disorders in a referral Children’s Hospital in Iran from 1997-2006, were investigated in this study. According to the World Health Organization classification, 27 patients were in class 1, followed by 6 patients in class 2, and 1 patient in class 3. Moreover, 1 patient was diagnosed with sinus histiocytosis with massive lymphadenopathy. Bone lesions were the most common manifestation, which were detected in 15 cases, followed by skin lesions (11 cases) and fever (10 cases). Nonspecific findings like hepatomegaly and splenomegaly were found in 15 cases. Different types of treatment protocols were used according to the diverse groups of histiocytic disorders and different stages of disease, including surgical excision, radiotherapy, chemotherapy, and stem cell transplantation. Twelve patients did not respond well to the treatment and subsequently died due to complications of their disease. Although histiocytosis is considered a rare condition, it can be problematic for pediatric hematologists because of the unknown etiologies and pathogenesis, variable classifications and subtypes, diagnostic difficulties, poor therapeutic responses with high mortality, and some complications after different therapeutic protocols.